Pengujian Kualitas Bibit Jabon Merah (AnthocephalusÃ‚Â macrophyllusÃ‚Â (Roxb.) Havil) pada Pemberian Pupuk Hayati dan Kimia - Irmayanti, Laswi; Nurhikmah, Nurhikmah; Fatrawana, Adesna (Cannarium, 2020)
Seedling quality is an expression used to describe a seedling ability to adapt and grow after planting. Good quality seedling will determine the success of planting. The purpose of this study was to describe the quality of Jabon seedling (Anthocephalus macrophyllus) in the application of biological and chemical fertilizers. The research was conducted at Tembal Lestari Nursery, South Halmahera Regency. The treatments applied were control, application of chemical fertilizers, biological fertilizers, and a combination of biological chemical fertilizers. The results of seedling testing on the combination of biological and chemical fertilizers gave a value of 100% according to the general requirements for seedling quality, and 100% included in the first class category (P) in the special requirements assessment.